Disparities in NIH funding for epilepsy research - Meador, Kimford J. (Lippincott Williams & Wilkins, 2011)
Using data from NIH Research Portfolio Online Reporting Tools (RePORT) and recently assembled prevalence estimates of 6 major neurologic diseases, we compared the relative prevalences and the annual NIH support levels for 6 major neurologic disorders: Alzheimer disease, amyotrophic lateral sclerosis (ALS), epilepsy, multiple sclerosis, Parkinson disease, and stroke. Compared to these other major neurologic disorders, epilepsy research is funded at a persistently lower rate based on relative disease prevalences. Relative NIH funding for these other disorders in 2010 adjusted for prevalence ranged from 1.7x (stroke) to 61.1x (ALS) greater than epilepsy. The disparity cannot be explained by differences in the overall impact of these diseases on US citizens. Greater transparency in the review and funding process is needed to disclose the reason for this disparity.